The Influence Of Motivation And Work Discipline On The Performance Of Traffic Unit Members Of Bekasi Metro Police - Lestari Ningsih; Harries Madiistriyatno; I Gede Adiputra (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to determine how much influence Motivation and Work Discipline have on the Performance of Traffic Unit Members of Bekasi Metro Police. Good motivation and work discipline are predicted to be variables that can continuously improve member performance. The author's purpose in conducting this study was to determine and analyze motivation, work discipline and member performance as well as the magnitude of the influence of motivation and work discipline on the performance of Traffic Unit members of Bekasi Metro Police, both simultaneously and partially. The method used in this study is a method with a quantitative descriptive approach. The sample in this study was 36 members of the Traffic Unit of Bekasi Metro Police. The data in this study are primary data, where the data was obtained from respondents' answers to the questionnaire that the author distributed. Based on the data analysis results that the author has done, it was found that there is an influence of motivation and discipline on the performance of Traffic Unit members of Bekasi Metro Police, both partially and simultaneously. Member performance is influenced by motivation and discipline variables by 56.6% and the remaining 43.4% is influenced by other factors not examined in this study.